Perhitungan Gear Sprocket pada Sepeda Motor Honda Blade 110CC Tahun 2012 - Muhammad Andreansyah; Kardiman Kardiman; Viktor Naubnome (Jurnal Ilmiah Wahana Pendidikan, 2022)
A sprocket is a serrated wheel that is attached to a chain, track, or other long serrated object. Sprockets are different from gears. Sprockets never come into contact with other sprockets and never match. Sprockets are also different from pulleys in that sprockets have teeth while pulleys generally do not have teeth. Sprocket is one of the components of a motorcycle that is paired with a chain that is used to transmit rotary force from the engine to the rear wheels. The purpose of this research is to obtain analysis and calculation of the diameter of the sprocket and the analysis that occurs in the chain. From the results of the calculation on the gearsprocket above, if the power generated by the motorcycle is 11.9 hp at 7500 rpm (maximum rotation) and the torque produced is 0.83 kgf.m at 5500 rpm, the resulting motorcycle sprocket diameter is 15. eye size (????1) = 45,836 , diameter of motorcycle gear with 45 points (????2) = 136,618 , average speed of chain (????) = 17,868 /????, average circumference force(????) = 496,4181 , the additional centripetal force of 420 N becomes, 825N, Chain length (m) = 1.09 m.